2016
DOI: 10.1017/s1368980016002044
|View full text |Cite
|
Sign up to set email alerts
|

How do we actually put smarter snacks in schools? NOURISH (Nutrition Opportunities to Understand Reforms Involving Student Health) conversations with food-service directors

Abstract: Objective: In autumn 2012, Massachusetts schools implemented comprehensive competitive food and beverage standards similar to the US Department of Agriculture’s Smart Snacks in School standards. We explored major themes raised by food-service directors (FSD) regarding their school-district-wide implementation of the standards. Design: For this qualitative study, part of a larger mixed-methods study, compliance was measured via direct observation of foods and beverages during school site visits in spring 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Sixteen papers were included in the review representing 15 separate initiatives. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen papers were included in the review representing 15 separate initiatives. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the sample characteristics, study design, and findings of included studies is shown in Table 4 (and Appendix S5). Five studies were conducted in the USA, 25,28,34,37,39 five studies in Australia, 24,26,27,35,38 one in Norway, 33 two studies in the Netherlands, 29,31 one in Korea, 32 and two in Canada. 30,36 Three initiatives were implemented exclusively in primary schools; 24,35,38 eight initiatives were implemented across a combination of primary, middle, and high schools; [25][26][27]30,32,33,36,37 and five initiatives were implemented exclusively in high schools.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Food service directors indicated that ensuring that competitive foods aligned with the multiple aspects of the updated standards (including calories, caffeine levels, and portion sizes that varied by grade level) could be challenging, especially without sufficient training, resources, and/or support from the school district. Food service directors reported that it was easier to comply with the standards when reference lists for compliant foods were used (e.g., John C. Stalker A-List), when the district had strong wellness policies, and when they were able to work with their district’s wellness committee to ensure compliant foods were sold [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NOURISH (Nutrition Opportunities to Understand Reforms Involving Student Health) Study was developed to learn more about the impact of the Massachusetts competitive food law on school compliance, 10,11 barriers and strategies for successful implementation, 12 revenues, 13 and students’ diets. This observational cohort study was a collaboration among the Harvard T. H. Chan School of Public Health, Northeastern University, Brandeis University, and the Massachusetts Department of Public Health.…”
mentioning
confidence: 99%